Analisis Kemampuan Pemecahan Masalah Matematika Siswa Kelas IX SMP Ditinjau Dari Gender - Nopia Rizki; Sudi Prayitno; Nurul Hikmah; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2021)
The aim of this study was to describe the differences of students' problem-solving abilities in completing mathematics problem in the form of story-based problems in terms of gender difference. The type of research used is qualitative and quantitative descriptive research using research instruments, namely tests of problem-solving abilities and interview. Selection of subjects using a random cluster random technique, based on teacher considerations. The subjects in this study were 26 students of class IX of SMPN 8 Mataram in the academic year of 2020/2021. The data collection method started from making observations at school, then distributing the problem-solving ability test which contains 2 problems in the form of elaborative questions. AT the last stage, the researcher conducted interviews with 6 people who were obtained from each representative of the criteria for the test results of the problem-solving abilities that had been given. The data analysis technique in this study was conducted by looking at the test scores of mathematics problem-solving abilities seen from the criteria of high, moderate, and low. The results obtained were: (1) the ability of female students in grade IX at SMPN 8 Mataram to solve mathematics problems related to the statistical topic in form of story-based problems was in moderate criteria with the average score obtained was 73.44, (2) the ability of male students in grade IX at SMPN 8 Mataram to solve mathematics problems related to the statistical topic in form of story-based problems was in moderate criteria with the average score obtained was 77,64, and (3) the difference in problem-solving abilities of male and female students lies on the steps used in solving mathematics problems based on Polya problem solving stages.